Montelukast as an Alternative to Low-Dose Inhaled Corticosteroids in the Management of Mild Asthma (The SIMPLE Trial): An Open-Label Effectiveness Trial - R Andrew McIvor; Alan Kaplan; Caroline Koch; John S Sampalis (Canadian Respiratory Journal)
OBJECTIVE: To evaluate the effectiveness of montelukast as monotherapy for patients with mild asthma who remain uncontrolled or unsatisfied while on inhaled corticosteroid (ICS) monotherapy.